Sustainable Management Coping with the Dilemmas of Resource-Oriented Management - Müller-Christ, Georg; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg Imprint: Springer, 2011)
In this book, a resource-oriented perception of sustainable management is presented. Firms that decide to act more sustainable have to bear in mind that they do not only need resources for economic activities today, but that they will need these tomorrow as well. This leads to contradictory management rationalities firms must deal with. The author presents his findings as regards the development of environmental and social responsibility and introduces a theory of management ecology. He takes a close look at the contradictions businesses have to face when governing their activity towards sustainability. Moreover, he identifies different notions of the resource term in management studies and develops a ?sustainable resource management? which could help businesses redirect their economic activities from a solely profit-oriented to a resource-oriented way of operating.
Introduction. - Part I: Understanding Sustainability. - 1 Sustainability and Society. - 2 Quo Vadis, Environmental Management?. - 3 Quo Vadis, Social Responsibility?. - 4 Sustainability as Economic Rationality. - Part II: Theoretical Impulses. - 5 A Theory of Management Ecology. - 6 Dominant Management Rationalities and the Necessary Improvements for a More Sustainable Management. - 7 Coping with Contradictions as Core Problem of Modern and Sustainability-oriented Management Studies. - Part III: Sustainable Resource Management. - 8 The Use of the Term ?Resource? in Management Studies. - 9 Salutogenesis as Heuristic for Resource-oriented Management Studies. 10 Strategic Resource Management
Electronic reproduction.
Keywords: Sustainable development; Resource allocation; Management -- Environmental aspects; Decision making; Electronic books